(untitled) (Scientiae Studia, 2012)
The transformations undergone by research and science in the name of the so called "knowledge economy" cover the decisions of scientific policies and the "management" of research, and also the meaning of scientific activities (devoted to innovation) and even more fundamentally the very structure of the sciences (transformed to technosciences). The science that is contributing to capitalist competitiveness (and to the current economic crisis) is not the same as that which would be able to contribute "to the conception and democratic carrying out of another form of globalization and another European project". However, this is not self-evident, and it needs to be thought about since it is not simply a matter of returning to the science of the 20th century that opened the way to technoscience.